Paul’s Use of Jewish Traditions - Bosman, Stefan (Tyndale bulletin, 2018)
By Stefan Bosman. A dissertation examining Paul’s use of Jewish traditions with particular reference to 1 Corinthians 10:4, Galatians 6:16, and Romans 5:12-21.